2020
DOI: 10.17576/3l-2020-2603-12
|View full text |Cite
|
Sign up to set email alerts
|

Expertise and Explicitation in English Translations of the Holy Quran

Abstract: With universals of translation budding into an interesting field in translation studies, discussing the nature of translation universals and explicitation as one of the universals of translation emerges as one important strand worthy exploring. In this paper, first of all, the notion of explicitation in translation is introduced, followed by the probable relations between expertise and explicitation discussed in two Arabic-English translations of the Holy Quran. First, a comparison was made between the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Anacoluthon is found by Darir (2012) to be a guise of explicitation according to which the TT is more explicit than the ST, a finding in line with Bisiada (2016) who proves that sentence splitting is an explicitating strategy rather than a process triggered by the target language. This finding is strongly supported by Raoufkazemi et al (2020) who revealed that the texts rendered by experienced translators are more explicit than the original.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Anacoluthon is found by Darir (2012) to be a guise of explicitation according to which the TT is more explicit than the ST, a finding in line with Bisiada (2016) who proves that sentence splitting is an explicitating strategy rather than a process triggered by the target language. This finding is strongly supported by Raoufkazemi et al (2020) who revealed that the texts rendered by experienced translators are more explicit than the original.…”
Section: Discussionmentioning
confidence: 55%
“…The Qur'anic text attracts so riveting and scrupulous research that each of its linguistic phenomena may be subjected to many scholarly endeavours (see Mohaghegh & Pirnajmuddin 2013, Abdul-Ghafour et al 2019, Raoufkazemi et al 2020, Alduhaim 2021. Abdul-Raof (2001: 68) argues that the Qur'anic language is characterised by rhetorically, syntactically, semantically, phonetically, and pragmatically idiosyncratic and prototypical features which render it roughly (un)translatable.…”
Section: Introductionmentioning
confidence: 99%
“…Translation is a communicative act that serves as a bridge connecting the target audience with the source audience via the use of a different linguistic system (Raoufkazemi et al, 2020). In the words of Abdul-Raof (2001, p. 1), the translation of the Quran is considered a "major human contribution in cross-cultural interfertilization; it is a unique charity to humanity".…”
Section: Introductionmentioning
confidence: 99%
“…Good translation skills are also inseparable from the translator's skills to divert the meaning and aesthetic elements. Raoufkazemi et al (2020) added that accurate translation is an inherently interdisciplinary effort. Many references can be used when we want to understand the meaning of a translation.…”
Section: Introductionmentioning
confidence: 99%